Perancangan Alat Pendeteksi Kebocoran Gas LPG Berbasis Arduino dengan Pendekatan Ergonomi - Mauluddin, Yusuf; Hamidah, Sabrina (Jurnal Algoritma, 2025)
LPG gas leaks in households are often found to be the cause of house fires. This study aims to design an Arduino-based LPG gas leak detector by applying ergonomic principles, both physical and cognitive, to improve user safety and comfort, especially in the household environment. Using the Ergonomic Function Deployment (EFD) method, the device design is tailored to the user's body dimensions and sensory abilities. This device is capable of effectively detecting gas leaks, providing warnings through sound alarms, indicator lights, and smartphone notifications. The results of the study show that the designed device is not only ergonomic, but also more efficient and safer than similar existing products. This product is expected to prevent potential fires caused by LPG gas leaks and improve safety in the household environment.